Mrs Donati feted (Raton Range Raton, New Mexico, 1980)
Newspaper Article on the 93rd birthday of Helen Donati.
Master list item #: 43
File location is in the Raton File Cabinet
Keywords: Donati, Helen; Pappas, Mike; King, Bruce; Fromm, Sabastian; Fromm, Madelyn; Donati, Frank; Donati, Angelo; Pais, Ermey; Bisetti, Marie; Chicarelli, Ellen; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Friedorf, Austria; Pittsburgh; Baltimore; Chicago; Colorado; California; Arizona; Florida